Spatial variations of Rn and CO2 emissions in the Wuzhong–Lingwu region, northwest China - Li, Xinyan; Liu, Xiaopeng; Zeng, Xianwei; Wang, Xiaotao; Luo, Hengzhi; Li, Mengya; He, Jiawei; Shi, Haikuo (Frontiers in Earth Science, 2023)
Soil gas Rn and CO2 in surface rupture and deep-seated fault zones are important indicators for tectonic and seismic activities. The spatial distributions of Rn and CO2 concentrations and their relationships with earthquakes and stress state in the Wuzhong–Lingwu area of Ningxia, Northwest China, were investigated through field observations based on 76 measurement points, spatial interpolation and six crossing-fault profiles along Yellow River Fault zone (YRF). Observed results of the soil gas Rn and CO2 in different segments of Yellow River Fault zone illustrated that YRF has features of both strike-slip and certain normal fault characteristics. Moreover, the difference in seismic activity could also account for the differences in gas concentration and relative activity intensity (RAI) in the Yellow River Fault zone. Significant differences in the spatial distributions of Rn and CO2 were identified in gridded observation mode. By comparing these spatial distributions with the surface latent heat flux (SLHF), volumetric soil water layer (SWVL), and lithology, an anomalous high-Rn area was identified in the east and south Qingtongxia, and associated with Permian sandstone and mudstone in a piedmont setting. Away from a strong impact of irrigation in the Yinchuan Basin, CO2 anomalies were identified in the transition area between the Yinchuan Basin and the mountains and coincided with a dramatic negative variation of surface latent heat flux, which was considered to reflect humus accumulation, rich organic matter, and strong soil microorganism activity in loosely accumulated mountain alluvial deposits. After excluding gas anomalies related to shallow soils and surface geology, anomalies of Rn and CO2 in the west of Lingwu were consistent with the distribution of low seismic b-values and frequent seismic activity in plane and profile. According to similar studies in the north-south seismic belts, it is believed that high stress and strong seismic activity increased the permeability of rocks and boosted the gas emission in the west of Lingwu. Base on a crustal thickness variation belt, high-velocity bodies, and in this region, an higher seismic hazard was illustrated. This study offers new insight into combining geochemical characteristics of soil gas and seismological methods to estimate regional seismic hazards.